2021
DOI: 10.1016/j.smrv.2021.101556
|View full text |Cite
|
Sign up to set email alerts
|

Improving sleep quality leads to better mental health: A meta-analysis of randomised controlled trials

Abstract: The extent to which sleep is causally related to mental health is unclear. One way to test the causal link is to evaluate the extent to which interventions that improve sleep quality also improve mental health. We conducted a meta-analysis of randomised controlled trials that reported the effects of an intervention that improved sleep on composite mental health, as well as on seven specific mental health difficulties. 65 trials comprising 72 interventions and N = 8,608 participants were included. Improving sle… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
287
1
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 396 publications
(296 citation statements)
references
References 180 publications
3
287
1
5
Order By: Relevance
“…Additionally, a systematic review by Spijkerman et al, [ 72 ] identified that online mindfulness interventions had benefits for depression and stress reduction [ 72 ]. Similarly, a 2021 meta-analysis of randomised controlled trials demonstrated that improving sleep quality improved mental health, including depression, anxiety, rumination and stress [ 69 ]. These findings are in line with a large meta-review of lifestyle psychiatry interventions which showed the critical role of modifiable lifestyle factors including physical activity, sleep, diet and smoking in the prevention and treatment of mental disorders [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a systematic review by Spijkerman et al, [ 72 ] identified that online mindfulness interventions had benefits for depression and stress reduction [ 72 ]. Similarly, a 2021 meta-analysis of randomised controlled trials demonstrated that improving sleep quality improved mental health, including depression, anxiety, rumination and stress [ 69 ]. These findings are in line with a large meta-review of lifestyle psychiatry interventions which showed the critical role of modifiable lifestyle factors including physical activity, sleep, diet and smoking in the prevention and treatment of mental disorders [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both decreased sleep duration or quality can adversely impact mental health [ 3 , 4 ], and conversely, most mental health disorders present with objective or subjective alterations in sleep [ 2 , 5 ]. The causal relation between altered sleep and decreased mental health is evidenced by the fact that improvements in sleep translate to improvements in mental health such as depression, anxiety, rumination and stress [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, research indicates that sleep quality reduces depression, anxiety, and stress [ 49 ]. Nevertheless, a few studies have also indicated a bi-directional relationship between sleep quality and anxiety [ 50 , 51 ].…”
Section: Introductionmentioning
confidence: 99%